The impact of abnormal maternal body mass index during pregnancy on perinatal outcomes: A retrospective cohort study - Ghinwa Lawand (17075043) (2023)
Background Abnormal Body mass index (BMI) during pregnancy is a growing public health concern as it has been associated with an increased risk of maternal and neonatal complications. This study aimed to investigate the impact of abnormal BMI on maternal and neonatal outcomes compared to normal BMI. Methods A total of 14,624 singleton births were included in a retrospective cohort study conducted in a tertiary maternity hospital in Qatar. Women were categorised as underweight (BMI <18.5 kg/m2), overweight (25.0-29.9 kg/m2), obesity class I (30.0– 34.9 kg/m2), obesity class II (35.0– 39.9 kg/m2), and obesity class III (≥40.0 kg/m2) and compared to women with normal BMI (18.5-24.9 kg/m2). Outcomes included gestational diabetes (GDM), gestational hypertension (GHT), postpartum haemorrhage (PPH), cesarean delivery (CD), preterm birth (PTB), low birth weight (LBW), congenital anomalies and neonatal intensive care unit admission. Results Compared to women with normal BMI, women with increasing BMI had increasingly higher odds of developing specific adverse outcomes, the highest being in the class III obesity group (GDM- aOR 2.71, 95% CI 2.25-3.27, p<0.001, GHT- aOR 5.32 95% CI 3.49-8.11, p<0.001, CD- aOR 2.33 95% CI 1.85-2.94, p<0.001, PPH- aOR 1.77 95% CI 1.35-2.33, p<0.001). On the other hand, being underweight during pregnancy was associated with an increased risk of PTB (aOR 2.09, 95% CI 1.37-3.20, p=0.001), LBW (OR 1.88, 95% CI 1.27-2.79, p=0.002) and congenital anomalies (aOR 2.52 95% CI 1.12-5.64, p=0.025). Nearly 67% of women in the underweight category gained less than the expected gestational weight gain during the pregnancy. Conclusion The findings of this study have important implications for the clinical management of pregnant women with abnormal BMI. They suggest that interventions to improve maternal and neonatal outcomes are crucial in directing prenatal care optimisation, focusing on enhancing prepregnancy BMI to minimise adverse maternal and neonatal outcomes.